Anteseden Kepuasan dalam Membentuk Loyalitas Pelanggan - Chrestina, Yohana Angel; Rahadhini, Marjam Desma; Sriwidodo, Untung (Benefit: Jurnal Manajemen dan Bisnis, 2017)
Chocolate provide many health benefits when consumed in enough, such as reducing stress, lowers blood pressure, improves blood circulation, reduces the risk of cancer. So that processed chocolate has the opportunity to serve as the culinary field effort. Diverse menu flavored drinks provided by Franchise Chocolate Classic, to the satisfaction of chocolate drink lovers. The purpose of this study to analyze the antecedents of satisfaction (menu diversity, trust, and customer value) in the form of customer loyalty. Collecting data using primary and secondary data. The sampling method using a non-probability sampling with purposive sampling of 140 respondents. Validity and reliability using confirmatory factor analysis (CFA) and cronbachs alpha. Methods of data analysis using Structural Equation Modeling (SEM). The findings of the research there is the influence of the diversity of the menu, the value of customers satisfaction, there is no effect of trust on customer satisfaction, there is the influence of satisfaction on loyalty, there is the influence of the diversity of the menu on loyalty, there is no influence of the value of customer loyalty, satisfaction mediates the effect of the diversity of the menu and confidence customer loyalty, satisfaction does not mediate the effect of customer value on loyalty. Advice for Chocolate Franchise Classical Solo to pay attention to the diversity of the menu, keep the trust and customer value so as to encourage consumers to buy again, recommend to others and be loyal.